Predição de valores genéticos de famílias e estrutura populacional de genitores em cana-de-açúcar (Saccharum spp.) usando marcadores microssatélites - Zeni Neto, Hugo (2011)
The success of a program of genetic improvement of sugarcane (Saccharum spp.) resides in the ambition of parents choosing the richest and most genetically divergent. One of the problems encountered in these programs of genetic improvement of sugarcane, is that in the early stages of selection, tend to be evaluated traits with low heritability, so it comes to preferring the adoption of the procedure for selection of families instead of mass selection. The present work aimed to select the best families of sugarcane that make up the RB05 Series of RIDESA adopting the methodology of mixed models (REML/BLUP) in two crops, as well as in joint analysis, estimate the genetic divergence and population structure that made up this series by the use of microsatellite markers (SSR). The experiment consisted in an incomplete block design with 78 families making up the series RB05, phase T1 of PMGCA/UFPR/RIDESA, five replicates per family and are considered together the data from the agricultural years 2008/2009 and 2009/2010. The characteristics evaluated were BRIX, tons of sugarcane per hectare (TCH) and ton of Brix per hectare (TBH). The top three families were for BRIX F41M60, F02M77 and F41M82 to TCH were F66M30, F35M06 and F78M45, and to TBH were F66M30, F35M06 and F78M45. The joint analysis proved to be a primary tool for use by breeders in the application of the families? selection, because there may be different ordering of the best families throughout the seasons. In the evaluation of molecular genetic diversity and population structure of 82 accessions of sugarcane, which are the parents of families RB05 Series, through the use of 36 primers microsatellites (SSR) demonstrated, under the use of the similarity coefficient Jaccard and UPGMA method, a cluster divided into 17 distinct groups. The primers showed 319 alleles, ranging from 2 to 19 loci with an average of 8.86 per primer. The PIC values ranged from 0.1527 to 0.9264 with an average of 0.5705. The corresponding similarity coefficient used demonstrated that the degree of similarity ranged from 0.4716 ix (RB965586 x RB971551) to 0.9526 (RB936001 x SP89-1115) with an average of 0.8536 showing a high similarity among the 82 individuals analyzed. The results indicate that SSRs can be used for construction of divergent groups of sugarcane to be used in future crosses between cultivars in the next little bit similar to each other to generate individuals with a high heterotic degree.